Effect of rope jumping exercise on foot arch in boy students with cavus, planus, and normal foot types - Mehdi Ghaderiyan; Gholam Ali Ghasemi; Vahid Zolaktaf (Vesnu Publications, 2015)
Introduction: The plantar arch is an architectural structure consisted of several joints, ligaments and muscles. It builds a functional unit that plays a vital role in weight bearing activities such as rope jumping. In this study, the effects of 12 weeks rope jumping on plantar arch in boy students with low, moderate, and high foot arches were evaluated. Materials and Methods: It was a controlled experimental study. At the beginning of study, the plantar arches of 450 boys (aged 10 to 13 years) were evaluated by Staheli index. Accordingly, 30 participants were recruited from every group with low, moderate, and high foot arches, provided their parents signed the informed consent form. Then, subjects of each study group were randomly assigned into control and experimental groups (n=15). Experimental groups took part in a 45- minute rope jumping program of 3 sessions per week, lasting for 12 weeks. Data were statistically analyzed by the use of Mixed ANOVA, using SPSS 22 software. Results: Compared to pre-test, post-test scores of plantar arch showed no difference in any control groups, nor in moderate-arch and high-arch experimental groups, but it showed significant increase in low-arch experimental group (p<0.01). Conclusion Our findings demonstrated that rope jumping exercises could improve plantar arch in boy students 10-13 years old with flexible flat foot. Therefore, we recommend such exercises to boy adolescents and call for the same study on girl adolescents. Keyword: rope jumping exercise, plantar arch, student, flat foot (pes planus), pes cavus.